Pengembangan Desain Layout Master Plan Lingkungan Dusun Sumberjambe Desa Srigonco Kabupaten Malang - Affan Bachtiar, Muhammad; Ali, Khoharudin; Nur Ibrahim, Izza; Alif Aditya, Muhammad; Al Ansyorie, Mohammad Musthofa (Universitas Ngeri Malang, 2023)
Srigonco Village is located on Malang Regency's coast, precisely in Bantur District. This village has several unique or distinctive characteristics that do not exist in other villages. This characteristic also adds to the attraction for tourists to visit Srigonco Village. The uniqueness or characteristic possessed is the strong Javanese cultural traditions in Srigonco Village, considering that this village is located on the edge of the South Malang coast. The increasing development of settlements in Srigonco Village is becoming a fundamental problem due to inappropriate spatial planning. To overcome the land problems in Srigonco Village, we developed an Environmental Master Plan Layout Design to Facilitate the Governance of Srigonco Village. The method used to develop a map of the area and population of Srigonco Village was updated by making a population plan using the cartometric measurement method. Apart from that, the process of determining regional boundaries can also be carried out using participatory mapping methods, where collecting data and information regarding regional boundaries involves active participation from the community and government officials as planners and information providers as well as mapping actors. The output of this activity is a final report in the form of an Environmental Master Plan Layout Map for Srigonco Village, Bantur District, and an ISBN journal regarding a design study for the development of an Environmental Master Plan Layout Design to Facilitate Srigonco Village Governance. So, this plan can support community and migrant activities and provide an opportunity for sustainable village development and improving village governance. Desa Srigonco merupakan desa yang terletak di pinggiran pantai Kabupaten Malang Tepatnya di Kecamatan Bantur. Desa ini memiliki beberapa keunikan atau ciri khas yang tidak ada di desa lainnya. Ciri khas ini juga menambah daya tarik wisatawan untuk berkunjung ke Desa Srigonco. Keunikan atau ciri khas yang dimiliki yaitu adat budaya jawa yang kental di Desa Srigonco mengingat desa ini berada di pinggiran pantai Malang Selatan. Semakin berkembangnya pemukiman di Desa Srigonco menjadi permasalahan yang mendasar dikarenakan rencana tata ruang yang tidak sesuai. Demi mengatasi permasalahan lahan yang terjadi di Desa Srigonco, kami membuat Pengembangan Desain Layout Master Plan Lingkungan Guna Mempermudah Tata Kelola Desa Srigonco. Metode yang digunakan untuk mengembangkan denah wilayah maupun penduduk Desa Srigonco yang diperbaharui dengan pembuatan denah penduduk menggunakan metode pengukuran kartometrik. Selain itu, proses penetapan batas wilayah juga dapat dilakukan dengan menggunakan metode pemetaan partisipatif, dimana proses pengambilan data dan informasi di lapangan mengenai batas daerah tersebut melibatkan partisipasi aktif dari masyarakat dan perangkat pemerintahan sebagai perencana dan pemberi informasi sekaligus sebagai pelaku pemetaan. Luaran dari kegiatan ini adalah laporan akhir yang berupa Peta Layout Master plan Lingkungan Desa Srigonco, Kecamatan Bantur, dan jurnal ber-ISBN mengenai kajian perancangan pengembangan Desain Layout Master Plan Lingkungan Guna Mempermudah Tata Kelola Desa Srigonco. Maka dengan adanya denah ini dapat menjadi sarana yang menunjang aktivitas masyarakat dan pendatang serta peluang untuk pembangunan desa yang berkelanjutan dan peningkatan tata kelola desa.